Tangible fixed assets For SME: Portuguese and Spain evidence - Marques, Maria Lúcia (2016)
The problem statement of this research is the application level of IAS 16 - Property, Plant and Equipment in SMEs provide by SME in Portugal and Spain. Indeed, the purpose of the research is comparing the accounting framework of IAS 16 - Property, Plant and Equipment in SME in Portugal and Spain. Also, it considers the information disclosure, conduct annually by the SME in both countries, comparing their similarities and differences. The methodology a used descriptive, pilot and explanatory analysis with support of a literature review of the normative and legal framework applicable to SME in the two countries. In addition, it understands the accounting changes resulting from legislation compared to previous normative. Indeed, it will be made an exhaustive documentary analysis of the content of the disclosure provided in the Annual Reports made by SME, through the Annex. The findings of the research allow to analyze the disclosure made by the SME and the applicable framework and the detail information about the IAS 16 - Property, Plant and Equipment. The main conclusion is centred on the Tangible Fixed Assets represent the largest percentage of assets in SME as collateral of financial decisions. Therefore, it allows stakeholders to take strategic decisions, including new investments.